Etiology and outcome of hematospermia :A prospective study - Karim Hadaia , Measar (Diyala Journal of Medicine, 2023)
Background: Although hematospermia is not common but considered an alarming symptom for patient and doctor. The cause of this worry is that it has been described as a dangerous symptom of prostate cancer by the patients and the health workers. Objective: To classify the causes and outcome of hematospermia. Patients and Methods: : This is a prospective study of patients newly diagnosed with hematospermia-diagnosed and treated in private clinic and hospital over a period of 4 years (2018-2022). Data collection and recording done related to demographic, symptomatology, clinical finding, investigations, treatment given and the outcome during 6 months of follow up. Results: One hundred and six patients with hematospermia were seen in the private clinic and hospital. The mean age was 40 years (25-70). Thirty-six (33.9%) patients were diagnosed as prostatitis clinically or by positive seminal fluid culture. Only (4) patients had prostate carcinoma with only one new case and the other three were known cases of prostate cancer already on treatment. With (4) cases had thrombocytopenia and (2) cases with sickle cell anemia and (1) case each prostate cyst and severe hypertension and vesical stone. (2) cases on anticoagulant therapy. And another (2) cases with history of epididymal surgery. There was no identifiable cause in the remaining 53 patients (50%). Conclusion: the majority of patients presented with hematospermia were below 50 years and have benign etiology and most of them were self-limited and less than 1% of cases revealed new prostate cancer. So, we can confidently reassure a patient presented with hematospermia due to benign nature of the disease in the majority of patients, especially in young patients.